Мохоподібні букових лісів на моніторинґовій трансекті „24 меридіян“ (відтинок Ґорґани — Передкарпатська височина) - Савицька, А. (Праці наукового товариства ім. Шевченка, 2008)
Мохоподібні букових лісів представленні 83 видами, що входять до 61 роду з 37 родин. Родини Brachytheciaceae і Plagiotheciaceae виявилися провідними за кількістю видів. Переважають епіксильні та епіфітні мохи. The flora of mosses in beech forests has been studied. As a results of our investigation, 83 species belonging to 61 genera and 37 families, has been recorded. Families Brachytheciaceae and Plagiotheciaceae include the largest number of species — jointly 18 ones. As to substrate distribution, the epixylic and epiphytic mosses are characterized by the largest species richness.